Aspects of a problem of energy security of Republic Moldova - Duca G.; Postolati V.; Bicova E. (Problems of the Regional Energetics, 2005)
The key positions and methodical aspects of a problem of energy security, the system of indicating devices is circumscribed, the state estimation of a power complex is made and the recommendations for a raise of energy security are offered.